1987
DOI: 10.1007/bf01942834
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition-deterring pheromone inRhagoletis cerasi L.: Purification and determination of the chemical constitution

Abstract: Summary. An oviposition-deterring pheromone (ODP) of the European cherry fruit fly Rhagoletis cerasi L. was isolated from faeces using cellulose and several reverse phase TLC and HPLC procedures. The biological activity was evaluated by means of behavior tests and by electrophysiological recordings from tarsal contact chemoreceptors. The compound was structurally characterized as a N[15(fl-glucopyranosyl)oxy-8-hydroxypalmitoyl]-taurine by spectroscopic means. The configurations of C-8 and C-15 of the fatty aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 9 publications
1
51
2
Order By: Relevance
“…A body of work that provides complete evidence of a MP is that of Boller, Hurter and colleagues on host-marking in the cherry fruit fly, Rhagoletis cerasi. These researchers isolated, characterized, and synthesized the MP utilized by R. cerasi and conducted behavioral assays that provide evidence that the synthesized compounds have an effect on female egglaying behavior similar to that produced by the mark itself (Hurter et al, 1987;Aluja & Boller, 1992;Boller & Aluja, 1992). From work on other closely related tephritid flies that host mark, the pheromone compounds are thought to be synthesized in the midgut (Prokopy et al, 1982a) and detected with chemoreceptors borne on the foretarsi (Crnjar & Prokopy, 1982).…”
Section: Eavesdroppingmentioning
confidence: 99%
“…A body of work that provides complete evidence of a MP is that of Boller, Hurter and colleagues on host-marking in the cherry fruit fly, Rhagoletis cerasi. These researchers isolated, characterized, and synthesized the MP utilized by R. cerasi and conducted behavioral assays that provide evidence that the synthesized compounds have an effect on female egglaying behavior similar to that produced by the mark itself (Hurter et al, 1987;Aluja & Boller, 1992;Boller & Aluja, 1992). From work on other closely related tephritid flies that host mark, the pheromone compounds are thought to be synthesized in the midgut (Prokopy et al, 1982a) and detected with chemoreceptors borne on the foretarsi (Crnjar & Prokopy, 1982).…”
Section: Eavesdroppingmentioning
confidence: 99%
“…The exact composition of the attractive blend of male-produced volatile molecules has not been established but has been proposed to be a complex blend of chemicals (Raptopoulos et al, 1995). The sex pheromone Hurter et al, 1987 composition is supposed to vary amongst Rhagoletis species, as sex pheromone constituents are usually synthesized from precursors taken from the host fruit (Landolt and Phillips, 1997), which differ among Rhagoletis species. Among the volatile chemicals identified in the headspace of R. cerasi, some have already been reported in other Tephritidae sex pheromones, such as geranyl acetate and (E,E)-a-farnesene, which have been reported as being constituents of the C. capitata sex pheromone (Heath et al, 1991).…”
Section: Mating and Sex Pheromonesmentioning
confidence: 99%
“…Fifteen years after the original suggestion of the existence of an HMP in a Rhagoletis species (Cirio, 1972;Prokopy, 1972), Hurter et al (1987) isolated, in the faeces of R. cerasi, a single compound named N[15(b-glucopyranosyl)oxy-8-hydroxypalmitoyl]-taurine. This chemical possesses two chiral centres (on carbon 8 and carbon 15), making it possible to exist as four different stereoisomers (Hurter et al, 1987).…”
Section: Oviposition and Host-marking Pheromonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, it was demonstrated that the application of HMP in cherry orchards reduced the R. cerasi infestation up to 90% 1980). On the 1980's, research efforts were made for the complete purification, chemical characterization and synthesis of the R. cerasi HMP, now also called of oviposition deterring pheromone (ODP) (Hurter et al 1976;Boller and Hurter 1985;Hurter et al 1987;Boller et al 1987;Ernst and Wagner 1989 (Hurter et al 1987). Subsequently, Boller and Aluja (1992) verified under laboratory conditions that the synthetic pheromone, isomer A (8R-15R) and the racemic mixture of the isomers A (8R-15R) + B (8S-15R) = 8RS-15R showed oviposition deterrence similar or higher than to the natural HMP.…”
Section: Hmp Application On the Integrated Managementmentioning
confidence: 99%